(untitled) (Sciences & Technologie. C, Biotechnologies, 2011)
Plasma was collected for hormone measurement from 150 Ouled Djellel ewe lambs, born in September, at 0 (< 24 hours), 1, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, and 26 weeks, and at 1 year of age. Four of the ewe lambs were slaughtered at each of the time points. The ovaries of the slaughtered lambs were weighed; antral follicles≥3mm in diameter were counted and their size was measured on histological ovarian sections. Concentrations of follicle stimulating hormone (FSH) and luteinizing hormone (LH) in plasma increased from birth to 10 weeks of age, and then declined to levels similar to those of yearling, sexually mature ewes. The level of LH then rose again to reach a second peak at 24 weeks of age, which represented the preovulatory LH surge. The variation in the concentrations of the hormones was accompanied by an initial increase in ovarian weight and maximum follicle diameter at 10 weeks of age, and a second increase in these ovarian characteristics at 18 weeks of age. These data suggest that Ouled Djellel ewes reach puberty early, at 24 weeks of age, and that there is a relationship between the variations in plasma concentrations of FSH and LH and the changes in follicular populations of antral follicles at certain ages.